CPT in polar snow - equipment and procedures - McCallum, A B; Barwise, A; Santos, R (CPT'10, 2010)
Although manual cone penetration testing in snow has been practised since the 1930’s, modern hydraulically-driven CPT equipment has not been used. Collaboration with the British Antarctic Survey will allow the first use of commercial CPT equipment in polar snow. This paper provides an introduction to polar snow, and outlines how existing CPT equipment has been adapted for Antarctic use. The interpretation techniques that will allow the determination of physical and mechanical properties of the snow pack are then briefly described. The knowledge gained through this research will contribute to improvements in design and construction of polar infrastructure.